2023
DOI: 10.3390/land12040816
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Changes in Cultural Landscape of Tourist-Type Traditional Chinese Villages from the Perspective of Cultural Memory: Taking Anzhen Village in Chongqing as an Example

Abstract: With the development of rural tourism, rural culture in China has suffered from development problems. Existing studies focus more on how to protect rural culture, ignoring the dynamic changes in rural culture. Therefore, cultural memory offers an important perspective to review the dynamic process of cultural changes. This paper uses the concept of cultural landscape to explore the changes in rural culture from the perspective of cultural memory. The research methods of historical data analysis and field inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… Culture change induced by rural tourism NO. Year Sub- topic Explanation Research method Primary Data source 48 2016 [ 134 ] Commoditization of Culture The process of tourism-induced commodification of culture and its impact on traditional villages (Mixed) ethnographic fieldwork/participant observation/interviews Villagers 49 2016 [ 131 ] (Mixed) semi-structured interviews/questionnaire/chi-square test Residents 50 2008 [ 127 ] Culture heritage continuity Aimed to identify the cultural creativity potentials and the change of traditional village induced by tourism (Qual) case study 51 2016 [ 128 ] (Qual) interview/observation Village leader/natives 52 2021 [ 72 ] (Qual) in- deep interviews/observation/the ethnography/grounded theory Villagers 53 2022 [ 130 ] (Qual) in- depth interviews/Participatory and non-participatory observations Tour guides and managers/tourists/mayors/homestay operators/villagers 54 2023 [ 129 ] (Qual) interviews/observation Villagers 55 2023 [ 135 ] (Qual) Historical data analysis/field investigation 56 2022 [ 133 ] …”
Section: Resultsmentioning
confidence: 99%
“… Culture change induced by rural tourism NO. Year Sub- topic Explanation Research method Primary Data source 48 2016 [ 134 ] Commoditization of Culture The process of tourism-induced commodification of culture and its impact on traditional villages (Mixed) ethnographic fieldwork/participant observation/interviews Villagers 49 2016 [ 131 ] (Mixed) semi-structured interviews/questionnaire/chi-square test Residents 50 2008 [ 127 ] Culture heritage continuity Aimed to identify the cultural creativity potentials and the change of traditional village induced by tourism (Qual) case study 51 2016 [ 128 ] (Qual) interview/observation Village leader/natives 52 2021 [ 72 ] (Qual) in- deep interviews/observation/the ethnography/grounded theory Villagers 53 2022 [ 130 ] (Qual) in- depth interviews/Participatory and non-participatory observations Tour guides and managers/tourists/mayors/homestay operators/villagers 54 2023 [ 129 ] (Qual) interviews/observation Villagers 55 2023 [ 135 ] (Qual) Historical data analysis/field investigation 56 2022 [ 133 ] …”
Section: Resultsmentioning
confidence: 99%
“…Chinese traditional villages, characterized by their "vernacular heritage" attributes, have garnered significant attention for their historical, cultural, social, and artistic values [5,6]. While sharing common issues with rural areas, traditional villages also face unique challenges related to cultural landscape changes [7], regional characteristic decline, and weak cultural identity [8,9], reflecting multiple dimensions of vulnerability and their association with "heritage".…”
Section: Introductionmentioning
confidence: 99%
“…Research on rural landscape planning has primarily focused on ecological conservation and recreational landscape planning. The proposed landscape planning systems have adequately incorporated ecological considerations, but it is necessary to establish management and monitoring mechanisms in the future to achieve the organic integration of landscape preservation and rural development [18,19]. Furthermore, studies have suggested classifying land based on its utility and employing different development patterns and management approaches to coordinate landscape ecological conservation with agricultural development [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%